Prevalence of Hyperuricemia and its Association with Sociodemography among Hypertensive Patients at Birat Medical College Teaching Hospital - Mehta, Ram Kumar; Mallick, Ram L; Parajuli, Surya; Jha, Rajneesh (Birat Journal of Health Sciences, 2021)
Introduction: Hypertension is the most common cardiovascular diseases. In only 5-10 % of hypertensive patients, underlying cause can be identified (secondary hypertension). Serum uric acid is thought to play a pathogenic role in development of hypertension and is also a commonly associated condition in patients with hypertension. Management of hyperuricemia will ultimately help in reducing cardiovascular morbidity and mortality. Objectives: To determine the prevalence of hyperuricemia among hypertensive patients atiending Birat Medical College Teaching Hospital and also to find association between hyperuricemia and socio-demographic variables. Methodology: This was a descriptive hospital based cross-sectional study conducted in 168 hypertensive patients at Birat Medical College Teaching Hospital, Nepal for a period of 6 months from 1 September 2020 to 28th February 2021. Sociodemographic variables were recorded and serum uric acid level was obtained based on the pre-structured questionnaires. Data were analyzed by Statistical Package for the Social Sciences version 20 (SPSS 20). Result: Prevalence of hyperuricemia was 42 (25%) among hypertensive patients with more prevalent in male 33 (30.8%) than female 9 (14.8%). Hyperuricemia was more prevalent in patients having higher BMI and patients aged more than 60 years i.e. 38 (34.5%) and 25 (41.7%) respectively. It was more prevalent among patients with hypertension for more than 15 years 10 (41.7%) and non-vegetarian 33 (25.8%). Hyperuricemia was significantly associated with those aged more than 60 years (p=0.002) and BMI >25 kg/m2 (p=0.002). Conclusion: Hyperuricemia was common associated condition among hypertensive patients. Hyperuricemia is mainly associated with male gender, non-vegetarian and patients with longer duration of hypertension. Similarly, it was strongly associated with older age and patients having higher BMI. Monitoring of serum uric acid and management of hyperuricemia might be helpful in management of hypertension and thus decreasing cardiovascular morbidity and mortality.